1994
DOI: 10.1038/bjc.1994.74
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of urokinase-type plasminogen activator (uPA) and plasminogen activator inhibitors PAI-1 and PAI-2 in breast carcinomas

Abstract: Summary It is now clearly established that proteolytic enzymes, including plasminogen activator (uPA), play an important role in breaking down the extracellular matrix, which is considered to be a step in metastasis formation. Plasminogen activators are controlled at various levels. Two inhibitors, PAI-1 and PAI-2, have been identified, the latter being more specific for uPA. In attempts to determine their prognostic value, it is essential to investigate the relative importance of these parameters and their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
84
3
3

Year Published

1996
1996
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 27 publications
12
84
3
3
Order By: Relevance
“…Urokinase and its inhibitors have been proposed as new prognostic factors in breast cancer (Duffy et al, 1990;Janicke et al, 1990;Foekens et al, 1992;Spyratos et al, 1992;Bouchet et al 1994;Foekens et al, 1995). However, their use for this purpose can only be envisaged once the results obtained with different assay methods have been compared.…”
Section: Discussionmentioning
confidence: 99%
“…Urokinase and its inhibitors have been proposed as new prognostic factors in breast cancer (Duffy et al, 1990;Janicke et al, 1990;Foekens et al, 1992;Spyratos et al, 1992;Bouchet et al 1994;Foekens et al, 1995). However, their use for this purpose can only be envisaged once the results obtained with different assay methods have been compared.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the role of urokinase-type plasminogen activator (uPA) and have described a correlation between uPA expression and cell invasion and metastasis (Foeckens et al, 1992). Type-1 plasminogen activator inhibitor (PAi-1) may also be directly involved in cancer progression, and an increasing number of clinical studies have demonstrated that high PAi-1 levels indicate a poor prognosis for the survival of patients suffering from a variety of cancers (Bouchet et al, 1994).…”
mentioning
confidence: 99%
“…When uPA complexes with PAI-i on the cell surface, it is internalized and degraded in a process mediated by uPA-R (Blasi, 1993). Recently, it was reported that tumour-associated uPA and PAI-I are strong and independent negative prognostic factors for breast cancer patients (Bouchet et al, 1994).…”
mentioning
confidence: 99%